Assessment challenges in the clinical environment - Du Plessis, M. A. (Faculty of Law, University of the Free State, 2009)
The assessment of students’ performance in the clinical legal education course presents a challenge for a variety of reasons. Factors to be considered are large student numbers, language barriers, a large and diverse client pool, students working in pairs, specialised units within the clinic, education and experience variances amongst students, different levels in students’ knowledge of substantive and procedural law, different levels of experience in clinical supervision and assessment, student expectations and prescribed exit-level outcomes for the course. The setting of parameters for assessment and mark allocation, as well as further methods of assessment, not currently used, are discussed.

Die beoordeling van studente se prestasie in the kliniese regskursus bied om verskeie redes sekere uitdagings. Faktore wat in ag geneem moet word, is groot studentegetalle, taalhindernisse, ’n groot en diverse kliëntebasis, studente wat in pare werk, spesialis eenhede binne die kliniek, ’n variasie in opvoeding en ondervindingvlakke onder die studente, die verskillende vlakke van studente se kennis van die substantiewe reg en prosesreg, verskillende vlakke van ondervinding in kliniese toesighouding en beoordeling, studenteverwagtinge en voorgeskrewe uitkomste vir die kursus. Die daarstel van ’n raamwerk waarbinne die beoordeling en puntetoekenning moet geskied, sowel as verdere beoordelingsmetodes, wat tans nie gebruik word nie, word bespreek.
Keywords: Clinical legal education; Student assesment; Legal education; Wits Law Clinic